2007
DOI: 10.1093/ndt/gfm707
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine-mediated improved response to erythropoietin involves induction of haem oxygenase-1: studies in humans and in an animal model

Abstract: These results are consistent with an involvement of HO-1 in carnitine's effect on erythropoiesis. The initial signals or effectors responsible for carnitine's effect remain to be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…[28] In the present study, the protective effect of L-carnitine against myoglobinuric renal injury was found to be more marked in the ARF-proLC group than in the ARF-LC group. It has been shown that the iron chelating effects of L-carnitine were concentration-dependent.…”
Section: Discussionsupporting
confidence: 46%
“…[28] In the present study, the protective effect of L-carnitine against myoglobinuric renal injury was found to be more marked in the ARF-proLC group than in the ARF-LC group. It has been shown that the iron chelating effects of L-carnitine were concentration-dependent.…”
Section: Discussionsupporting
confidence: 46%
“…The ability of carnitine to reduce oxidative stress via its effects on hemeoxygenase-1, which reduces the cytokine-induced alterations in cellular iron homeostasis, may form, at least in part, the basis for a greater sensibility/enhanced response to ESA treatment in HD patients [89] .…”
Section: -Carnitinementioning
confidence: 99%
“…The recently reported effect of the chronic administration of L‐carnitine of reduction of blood pressure and attenuation of inflammatory process associated with arterial hypertension in an animal model of L‐NAME‐induced hypertension 1 directly relates with two recent studies from our laboratory, 2,3 which are directly applicable and complete this observation. These studies, in fact, specifically address the issue of the effect of L‐carnitine on inflammatory markers and possible effect on renin‐angiotensin system, which was central in the effect of chronic administration of L‐carnitine on blood pressure and related inflammatory process.…”
mentioning
confidence: 65%